2006
DOI: 10.1889/1.2372416
|View full text |Cite
|
Sign up to set email alerts
|

MTF measurement method for medical displays by using a bar-pattern image

Abstract: -A modulation-transfer-function (MTF) measurement method that uses a bar-pattern image for medical displays such as liquid-crystal displays (LCDs) and cathode-ray tubes (CRTs) has been investigated. A specific bar-pattern image on the display was acquired with a high-resolution singlelens reflex-type digital camera equipped with a close-up lens. The MTF was calculated from the amplitudes of the fundamental-frequency components, which were extracted from the profile data across the bar patterns by using Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The MTFs of the LCD were measured using a bar-pattern image method proposed by Ichikawa et al 2 The close-up images of the displayed bar pattern were captured by a high-resolution single-lens reflex (SLR) digital camera (D80, Nikon Corporation, Tokyo, Japan) equipped with a close-up lens (Micro-Nikkor60 mm F2.8D, Nikon Co.). The camera has a charge-coupled device (CCD)-sensor array with a 3872 × 2592 elements and a contrast resolution of 12 bits.…”
Section: Iic1 Mtfs Of Lcdmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTFs of the LCD were measured using a bar-pattern image method proposed by Ichikawa et al 2 The close-up images of the displayed bar pattern were captured by a high-resolution single-lens reflex (SLR) digital camera (D80, Nikon Corporation, Tokyo, Japan) equipped with a close-up lens (Micro-Nikkor60 mm F2.8D, Nikon Co.). The camera has a charge-coupled device (CCD)-sensor array with a 3872 × 2592 elements and a contrast resolution of 12 bits.…”
Section: Iic1 Mtfs Of Lcdmentioning
confidence: 99%
“…Several researchers have already investigated and reported inherent image characteristics of various LCDs as modulation transfer function (MTF) and noise power spectrum (NPS), which are attributed to the matrix size, pixel-structure shape, aperture ratio, screen filter, etc. [1][2][3][4][5][6] Fur-ther, Bacher et al reported the observer-performance results of image characteristics on LCDs by using window setting and magnification. 7 In this study, we performed theoretical analyses for inherent image characteristics as well as the overall noise characteristics of displayed images on a LCD for varying magnifications.…”
Section: Introductionmentioning
confidence: 99%
“…On granularity measurement, an estimation pattern image was displayed on the monitor and photographed with a single-lens reflex digital camera, and the WS in a 100 9 100 pixel homogenous area displayed at a specific brightness was calculated from the raw CCD data. These measurement methods were adopted as simple, accurate methods for the physical evaluation of LCD panels [5,6].…”
Section: Evaluation Of Physical Characteristicsmentioning
confidence: 99%
“…Ichikawa et al measured the image characteristics of liquid crystal displays using a similar digital camera, and they demonstrated that the spatial resolution of the camera was sufficient to measure MTFs of objects. [18][19][20][21][22] The camera has charge coupled device ͑CCD͒, sensor arrays of 3008ϫ 2000 and a contrast resolution of 14 bits. The sampling pitch of the camera is about 0.08 mm on the plane of the film if the lens is adjusted with the highest magnification.…”
Section: Iib Mtfs and Presampling Mtfsmentioning
confidence: 99%